"Why Turn Me into a City Dweller?" Unveiling Public and Hidden Transcripts in Hygiene Promotion within an Impoverished Migrant Community. - Zou, Wenxue; Wu, Xinyun; Yan, Yan (Health Communication, 2026)
Inadequate hygiene is a key driver of adverse health outcomes among impoverished populations. In many underdeveloped countries, hygiene-focused health promotion programs are often integrated into broader poverty alleviation initiatives. Drawing on a critical health communication approach and Scott's framework of public and hidden transcripts, this study investigates hygiene promotion campaigns targeting rural migrants in China, led by poverty alleviation officials. Semi-structured interviews with 42 participants, including both officials and migrants, reveal divergent narratives surrounding these efforts. In the public transcript co-constructed by officials and the public, hygiene promotion is portrayed as a governmental endeavor aimed at benefiting the populace, garnering gratitude and support from impoverished migrants. This contrasts sharply with the hidden transcripts of both parties. Officials perceive hygiene promotion as a potent instrument capable of revolutionizing the perceived ignorant, backward, and disorderly agricultural lifestyle of migrants, thereby catalyzing a profound societal metamorphosis toward modernization. Nevertheless, migrants emphasize the autonomous and thoughtful nature of their hygienic choices. These findings uncover the modernization agenda underlying hygiene-based poverty alleviation, shedding light on the intricate dynamics of domination and resistance while critiquing how the imposed Western-centric framework marginalizes impoverished populations by undermining their cultural and social identities.